Collective individualities: cultural and political reception in Taiwan's history, architecture and cities - Lin, Francis Chia-Hui (Arq (London, England), 2014)
Reception is an idea which deals with the reinterpretation of knowledge. Reception therefore appears as an important issue in studies of historiography that see textual forms of history as representations of the past. Reception in history varies from agent to agent: different subjects who hold different ideological positions, in different positions with respect to power relations, receive the same object differently. Public reception, for instance, plays an important role in shaping the spatial representations of architecture and cities, which can be regarded as textual forms of history and therefore as a form of historiography which reinterprets and integrates the facts of the past. The work of Ackbar Abbas, in his depiction of the skyscrapers in Hong Kong which inscribe capitalism in the fabric of that city, offers a remarkable example. He illustrates how Hong Kong's spatial routine plays out in the reception of styles; for example, design oriented towards economy, the phenomenon of constant building and rebuilding, and the pursuit of hyper-density in Hong Kong's built environment. In different time periods, locations and cultural-political contexts, therefore, the public reception of architecture and cities differs. This paper takes Taiwan as an example. It examines a transformational period – from Taiwan's post-Second World War development to the present – scrutinising the reception of its history, architecture and cities.